2016
DOI: 10.1021/jacs.6b11673
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Enolates in the Enantioselective Construction of Tetrasubstituted Carbon Centers with Chiral Lithium Amides as Noncovalent Stereodirecting Auxiliaries

Abstract: Lithium enolates derived from carboxylic acids are ubiquitous intermediates in organic synthesis. Asymmetric transformations with these intermediates, a central goal of organic synthesis, are typically carried out with covalently attached chiral auxiliaries. An alternative approach is to utilize reagents that form discrete, well-defined aggregates with lithium enolates, providing a chiral environment conducive of asymmetric bond formation. These reagents effectively act as non-covalent, or traceless, chiral au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…[2] For example we now have methods for the direct α- alkylation of aldehydes [3] and carboxylic acids. [4] Thus it is perhaps surprising that the general, direct asymmetric alkylation (including allylation) of ketones remains elusive. Even the most simple asymmetric alkylation reactions involving ketones have not been reported (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[2] For example we now have methods for the direct α- alkylation of aldehydes [3] and carboxylic acids. [4] Thus it is perhaps surprising that the general, direct asymmetric alkylation (including allylation) of ketones remains elusive. Even the most simple asymmetric alkylation reactions involving ketones have not been reported (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas “masked” derivatives of carboxylic acids, such as esters and amides, have been frequently employed in stereoselective aldol reactions, asymmetric variants employing unprotected carboxylic acids have been rare . While the groups of Mulzer, Zakarian, and Fringuelli developed asymmetric aldol reactions of carboxylic acids, their procedures required stoichiometric amounts of chiral reagents to realize enantioselectivity (Scheme a, b). To the best of our knowledge, catalytic variants of asymmetric aldol reactions of carboxylic acids have not been reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas "masked" derivatives of carboxylic acids,s uch as esters and amides,h ave been frequently employed in stereoselective aldol reactions,asymmetric variants employing unprotected carboxylic acids have been rare. [4][5][6][7][8][9] While the groups of Mulzer, [4] Zakarian, [5] and Fringuelli [6] developed asymmetric aldol reactions of carboxylic acids,t heir procedures required stoichiometric amounts of chiral reagents to realize enantioselectivity (Scheme 1a,b). To the best of our knowledge,catalytic variants of asymmetric aldol reactions of carboxylic acids have not been reported to date.Considering the high demand for carboxylic acids,their direct catalytic aldol reaction represents an ew tool in complex molecule synthesis.Recently,Kanai and co-workers developed an asymmetric Mannich-type reaction of carboxylic acids by using ac ombination of catalytic borane and ac hiral binol, [10] but the reaction was limited to imine electrophiles,a nd the use of carbonyl electrophiles as aldol acceptors has remained difficult.…”
mentioning
confidence: 99%
“…Catalytic Chemoselective Activation of Carboxylic Acids promoting a catalytic asymmetric aldol reaction of carboxylic acids, 10 another fundamental and synthetically useful C-C bond-forming reaction. [11][12][13][14] Here we found that in-situ pre-conversion of carboxylic acids to siloxy esters dramatically facilitated the boron-catalyzed, carboxylic acid-selective asymmetric aldol reaction. The siloxy group worked as a traceless activator, allowing for the direct use of carboxyl group-containing multifunctional drugs and natural products themselves as substrates of catalytic asymmetric aldol reactions.…”
Section: Introductionmentioning
confidence: 99%